2016
DOI: 10.1002/etc.3238
|View full text |Cite
|
Sign up to set email alerts
|

Indirect photochemical transformations of acyclovir and penciclovir in aquatic environments increase ecological risk

Abstract: Acyclovir and penciclovir, 2 antiviral drugs, are increasingly detected in aquatic environments. The present study explores the natural photochemical transformation mechanisms and fate of these drugs, examining direct and indirect photochemical transformation under simulated sunlight irradiation. The 2 antiviral drugs are photostable under certain conditions but significantly degrade in the presence of chromophoric dissolved organic matter (DOM). The degradation rate associated with the drugs' indirect photoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Surface waters are impacted by a myriad of organic pollutants, including pharmaceuticals and pesticides . After their use in agriculture, stockbreeding, medicine, and industry, the chemicals enter surface waters through wastewater discharges or stormwater runoff. Studies have reported that photochemical reactions, including indirect photolysis pathways, where a photosensitizer absorbs light and generates reactive species, are important in the degradation of many organic pollutants. For example, photolysis of various pesticide classes has been investigated in prairie wetland surface waters, and Remucal found that indirect photolysis drives the aquatic fate of various pesticide classes . Understanding the photolysis of pollutants in surface waters is essential for assessing potential exposures and risks to aquatic organisms as well as to humans via drinking water supplies.…”
Section: Introductionmentioning
confidence: 99%
“…Surface waters are impacted by a myriad of organic pollutants, including pharmaceuticals and pesticides . After their use in agriculture, stockbreeding, medicine, and industry, the chemicals enter surface waters through wastewater discharges or stormwater runoff. Studies have reported that photochemical reactions, including indirect photolysis pathways, where a photosensitizer absorbs light and generates reactive species, are important in the degradation of many organic pollutants. For example, photolysis of various pesticide classes has been investigated in prairie wetland surface waters, and Remucal found that indirect photolysis drives the aquatic fate of various pesticide classes . Understanding the photolysis of pollutants in surface waters is essential for assessing potential exposures and risks to aquatic organisms as well as to humans via drinking water supplies.…”
Section: Introductionmentioning
confidence: 99%
“…72,109 For Environmental Science: Water Research & Technology Critical review instance, acyclovir, penciclovir and their substructural unit imidazole which are rich in electrons are identified as the reaction units for 1 O 2 through Diels-Alder reactions. 118 The diphenhydramine molecule is not rich in electrons, and quenching 1 O 2 enhanced its photodegradation rate, proving the insignificant roles of 1 O 2 . 32 3 DOM* is able to quench ˙OH, and MPs whose photolysis can be enhanced by ˙OH can therefore be inhibited by 3 DOM*.…”
Section: Radical Species Affecting Photodegradation Of Micropollutantsmentioning
confidence: 96%
“…72,109 For instance, acyclovir, penciclovir and their substructural unit imidazole which are rich in electrons are identified as the reaction units for 1 O 2 through Diels–Alder reactions. 118 The diphenhydramine molecule is not rich in electrons, and quenching 1 O 2 enhanced its photodegradation rate, proving the insignificant roles of 1 O 2 . 32…”
Section: Radical Species Affecting Photodegradation Of Micropollutantsmentioning
confidence: 96%
See 1 more Smart Citation